Impact of Baseline Tuberculin Skin Test and Isoniazid Chemoprophylaxis on Subsequent Quantiferon-TB Gold In-Tube Performance in Young Children Assessed After Tuberculosis Contact in Catalonia. Issue 2 (February 2020) - Velasco-Arnaiz, Eneritz; Soriano-Arandes, Antoni; Espiau, María; Altet, Neus; Fortuny, Clàudia; Monsonís, Manuel; Tebruegge, Marc; Noguera-Julian, Antoni
Abstract : We investigated the impact of baseline tuberculin skin tests (TSTs) and preventive isoniazid chemoprophylaxis on subsequent QuantiFERON-TB Gold In-Tube (QFT-GIT) assays performed after a 10- to 12-week window period in 114 children <5 years of age. Previous TSTs and chemoprophylaxis had no impact on the magnitude of subsequent antigen-induced responses in QFT-GIT. Furthermore, previous TSTs did not induce conversion from a negative to a positive QFT-GIT result. Abstract : Supplemental Digital Content is available in the text.